ANALISIS PERUBAHAN BENTUK DENGAN PENYEDERHANAAN KARAKTER WARAK NGENDHOG KE IP KARAKTER LEK JON DARI SECCON - Bayu Widiantoro (Universitas Katolik Soegijapranata, Semarang, 2021)
Many people feel that changing the shape or stylizing the shape of the character of the past object cannot be done because it will be able to change the message that will be conveyed through the existing traditional form. Meanwhile, this form that has existed in the past becomes a form that can be considered boring for the next generation because the shape is considered complicated and not up to date.The character of Lek Jon, which was developed by Semarang Creative Content as an IP character, is expected to be a bridge between the shape of the Semarang mascot which is derived from the mythical beast Warak and the current millennial target. The various stylized forms that were carried out then made some people feel that there were too many things that were not the same between the two. In this study, we will try to see by comparing the shape and proportion between Warak Ngendhog and the character of Lek Jon. And in this study a conclusion was obtained that body proportions have a big enough role to convey a message about a shape to the target.